Perspektif Mahasiswa Terhadap #KaburAjaDulu dalam Konteks Kewarganegaraan di Era Digital - Deva Lutfi Azizah; Elvira Ade Fadhila; Joko Tri Nugraha; Putri Ayu Amanda; Restu Sri Widyaningrum; Ridha Tsaniya Putri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The hashtag #KaburAjaDulu, which gained traction on social media in early 2025, embodies the unease and dissatisfaction of Indonesia's youth, especially university students, regarding the nation's socio-political and economic climate. This online manifestation signifies increasing disenchantment with systemic disparities, political inertia, and restricted economic prospects. This research seeks to analyze students’ interpretations of the hashtag through the lens of digital citizenship, emphasizing its role as a novel mode of civic participation in the contemporary digital landscape. A descriptive quantitative methodology was utilized, employing an online survey directed at students from diverse academic disciplines who actively engage with social media. A total of 55 participants were chosen through purposive sampling, based on their familiarity or involvement with the #KaburAjaDulu conversation. The data were processed using SPSS version 27, applying both descriptive and correlational analysis techniques. Results indicate that the majority of students do not view the hashtag as an indication of apathy, but rather as a thoughtful critique of the perceived shortcomings of national values like justice and meritocracy. Additionally, a positive correlation was identified between digital literacy and students’ critical perspectives on national matters. This implies that enhanced digital literacy fosters constructive engagement in digital environments. The research concludes that civic education must evolve with digital advancements by fostering contextual, interactive, and pertinent pedagogical methods. Such strategies are vital for cultivating digitally literate citizens who are critical, accountable, and actively involved in civic affairs.